Simultaneous removal of C, N, P from cheese whey by jet loop membrane bioreactor (JLMBR) - Farizoglu, Burhanettin; Keskinler, Bülent; Yildiz, Ergun; Nuhoglu, Alper (Elsevier Science Bv, 2007)
The membrane bioreactor (MBR) used in this study consisted of a jet loop bioreactor (aerobic high rate system) and a membrane separation unit (microfiltration). Jet loop membrane bioreactor (JLMBR) system is a high performance treatment system. High organic loading rates can be achieved with a very small footprint. The JLMBR is a compact biological treatment system which requires much smaller tank volumes than conventional activated sludge system. Solid-liquid separation is performed with a membrane. The JLMBR system, of 35 L capacity, was operated continuously for 3 months with a sludge age of 1. 1-2.8 days and chemical oxygen demand (COD) loads of 3.5-33.5 kg COD m(-3) day(-1). The mean concentration values of COD, total nitrogen (TN) and PO43- in cheese whey (CW) were found as 78,680 mg L-1, 1125 mg L-1 and 378 mg L-1, respectively. Ninety-seven percent COD removal rate was obtained at the sludge age (Theta(c)) of 1.6 days and volumetric loads of 22.2 kg COD m(-3) day(-1). TN removal was obtained as 99% at the loading rates of 17-436 g TN m(-3) day(-1). PO43- removals were between 65 and 88% for the loading of 30-134 g PO43- m(-3) day(-1). The system could simultaneously remove the COD, TN and PO43- at high efficiencies. The sludge flocks were highly motile, dispersed and had poor settling properties. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: jet hoop reactor; membrane filtration; Cheese whey treatment; biologic nutrient removal